RETRACTED: Harnessing AI Tools to Enhance English Writing Skills in Undergraduate Education - Ibrahim Mohammad, Suleiman; Shafiah, Waheed; Vasudevan, Asokan; Natarajan, Raja; Jamal, Afsha; Emmanuel Thella, Sunand; Shanthi William, Grace; Sasikanth Kambham, John Wesley (Forum for Linguistic Studies, 2025)
The article has been retracted titled “Harnessing AI Tools to Enhance English Writing Skills in Undergraduate Education”. The article has been retracted by agreement between the Authors, the Journal Editor-in-Chief, and the Publisher. Retraction Date: 5 December 2025